1973
DOI: 10.1002/j.1556-6978.1973.tb01596.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Characteristics and Effectiveness in Serving Economically Disadvantaged and Advantaged Males

Abstract: This study compared the personality characteristics, determined by the Sixteen Personality Factor Questionnaire (16 PF), of practicing junior and senior high school counselors serving economically disadvantaged and economically advantaged males. A Counseling Evaluation Inventory (CEI) composite client‐rating score, derived from seven male clients and determined for each counselor, was the effectiveness criterion. Male clients from both economic populations perceived as effective those male counselors who expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…However, neither this study nor Myrick, Kelly, and Wittmer (1972) found the substantial discrepancies in the traits of effective male and female counselors reported by McClain (1968). Shelton (1973) used a composite client-rating on the Counseling Evaluation Inventory (CEI) as the criterion of counselor effectiveness. A comparison of the 16PF scores of those rated more effective with those rated less effective produced the stereotypic masculine and feminine profiles earlier noted by McClain (1968) for the effective male and female subjects.…”
Section: Review Of Educational Researchmentioning
confidence: 77%
See 2 more Smart Citations
“…However, neither this study nor Myrick, Kelly, and Wittmer (1972) found the substantial discrepancies in the traits of effective male and female counselors reported by McClain (1968). Shelton (1973) used a composite client-rating on the Counseling Evaluation Inventory (CEI) as the criterion of counselor effectiveness. A comparison of the 16PF scores of those rated more effective with those rated less effective produced the stereotypic masculine and feminine profiles earlier noted by McClain (1968) for the effective male and female subjects.…”
Section: Review Of Educational Researchmentioning
confidence: 77%
“…While the scores on the GRE were unrelated to the CERS, a significant correlation (.41) was found between supervisor ratings on this scale and an index of predicted counseling effectiveness derived from the 16PF specification equation (McClain, 1968). Although, to the best of our knowledge, this combination of predictors from the 16PF has not been crossvalidated, this has not deterred its use in subsequent studies reported below (Shelton, 1973;Wehr & Wittmer, 1973). Myrick, Kelly, and Wittmer (1972) compared the 16PF scores of 40 student counselors who had been rated as either effective or ineffective by supervisors using the CERS.…”
Section: Review Of Educational Researchmentioning
confidence: 95%
See 1 more Smart Citation
“…Male and female school counselors displaying characteristics consistent with traditional sexual stereotypes tend to be more effective (Shelton, 1973). The same is true of effective students and effective paraprofessionals (Wittmer & Wehr, 1972).…”
Section: Evaluation and Accountabilitymentioning
confidence: 91%